MEKANISME PERTAHANAN EGO TOKOH AKU DALAM NOVEL SEMUSIM DAN SEMUSIM LAGI KARYA ANDINA DWIFATMA - Ahmad Supena; Firda Rastia (Universitas Sultan Ageng Tirtayasa, 2016)
The interrelation of literary with theory of personality can not be apart from character and characterization, both from the perspective of the authors, readers, or from a character in this literature. Novel as a “media delivery” author’s imagination through the characters and characterizations that are built into the story. While the characters and characterizations in the novel was formed to develop the story and reinforce the text content of the novel. Semusim dan Semusim Lagi novel by Andina Dwifatma, consider a most important tokoh aku as main character to build the “fantasmatik” affair. By a simple language style, tokoh aku handed over a behavior of the anxiety and the she was so fear that without a conscious she make a defense mechanism to relieve the tension of anxiety. On the basis of these explanations, the writer focus on the question of research on (1) the forms of defense mechanism the character ego in a novel entitled Semusim dan Semusim Lagi written by Andina Dwifatma, (2) the influence anxiety about defence mechanism of the character ego in a novel entitled Semusim dan Semusim Lagi written by Andina Dwifatma. This research method is descriptive analytical. This method is used because the writer explains the results of analysis. The technique used is data collection (books study, observe attentively, and record) and data analysis techniques that use is contents analysis. Sourch of the research is a novel entitled Semusim dan Semusim Lagi by Andina Dwifatma. Analysis result defence mechanism of the character ego tokoh aku in a novel Semusim dan Semusim Lagi written by Andina Dwifatma in the form of represi (repression), proyeksi, displacement, rationalization, regresi, fiksasi, and stereotype. And then, defence mechanism of the character ego tokoh aku because realistic anxiety, neurotic anxiety, and moral anxiety.